Lexical feature analysis of Chinese informed consent forms based on the information entropy methods: A paired study of minor and their guardian’ version - Qiansu Yang; Yining Wang; Wenbin Shi; Zhenzhen Li; Hong Liang; Jiang Cao; Nan Bai; Chien-Hung Yeh (PLoS ONE, 2025)
High-quality informed consent forms (ICFs) are crucial to facilitate effective communication between researchers and patients. However, the complex and specialized terminologies in ICFs often result in biased or late interpretations, thus hindering the ability to make decisions in line with their own will. Therefore, evaluating the readability of ICFs is an important task for Institutional Review Boards (IRBs) and regulatory agencies. This study proposes the use of information theory methods, including Shannon entropy and its extension—Rényi entropy ( α values = 0, 0.5, and 1.5), as a set of comparisons, to quantify the lexical characteristics of Chinese ICFs, for either minors or their guardians. The Shannon entropy and Rényi entropy values of minor-version ICFs were significantly lower than those of guardian-version ICFs. The Shannon entropy and Rényi entropy with α = 1.5 of the ICFs for minors show no significant differences compared to those of the sixth-grade textbooks, while the Rényi entropy with both α = 0 and 0.5 shows no significant differences compared to the ninth-grade textbooks. This study utilized information entropies to assess lexical features of ICFs, as a pilot study to validate the feasibility of implementing Shannon and Rényi entropies to evaluate readability in Chinese ICFs.